Composite binder as well as preparation method and application thereof

By preparing composite binders containing titanium and clay, the problem of titanium tetrachloride waste liquid produced during the preparation of polyolefin catalysts is solved, and the performance of catalysts and additives is improved, achieving the dual goals of environmental protection and resource utilization.

CN119909666APending Publication Date: 2025-05-02PETROCHINA CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311424362.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

During the preparation of polyolefin catalysts, a large amount of waste liquid containing titanium tetrachloride is generated, resulting in environmental pollution and waste of resources. In the prior art, the preparation process of kaolin modification and titanium-containing kaolinite is complex.

Method used

Using a method of preparing a composite binder, a composite binder containing titanium and clay is prepared by mixing the calcined clay, water and a titanium tetrachloride solution and reacting at 40-120°C for 0.5-6 hours. The composite binder containing titanium and clay is prepared, which comprises 7-45% by weight of titanium, 0.6-40% by weight of aluminum and 30-92% by weight of silicon.

Benefits of technology

This composite binder can improve the anti-wear properties, activity and pore volume of the catalyst and additives, promote efficient conversion of heavy oil, reduce coking, and improve the selectivity of the reaction process, solve the problem of waste liquid treatment and reduce the treatment cost.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a composite binder as well as a preparation method and application thereof. The preparation method comprises the following steps: (1) mixing roasted clay, water and a titanium tetrachloride solution to obtain a mixture; and (2) reacting the mixture at 40-120 DEG C for 0.5-6 hours to obtain the composite binder, calculated by taking the dry basis of the composite binder as 100%, the composite binder comprises the following components in percentage by weight: 7-45wt% of titanium in terms of oxide, 0.6-40wt% of aluminum in terms of oxide and 30-92wt% of silicon in terms of oxide. According to the preparation method, the problem of utilization of the titanium tetrachloride-containing waste liquid is solved, the waste liquid is prevented from polluting the environment, and the prepared composite binder can be used for preparing a catalyst and an auxiliary agent and can be used for improving the wear resistance, activity and pore volume of the catalyst and the auxiliary agent, improving the diffusion performance, promoting efficient conversion of heavy oil, reducing green coke and improving the selectivity and use performance of the reaction process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical engineering, and in particular relates to a binder containing titanium and modified clay, and a preparation method and application thereof. Background Art

[0002] In the process of industrial production of polyolefins, the widely used catalyst is mainly Ziegler-Natta catalyst, which is a titanium catalyst. Regarding the preparation of titanium polyolefin catalysts, for example, patent CN102336851B discloses a propylene polymerization catalyst, including magnesium, titanium, halogen and internal electron donor compounds diisobutyl phthalate, diethyl phthalate or di-n-butyl phthalate and a mixture of succinate; patent CN107434832B discloses a propylene polymerization catalyst, mainly composed of alcohol magnesium compounds, titanium compounds and phosphate electron donor compounds. The common method for preparing titanium catalysts at present is: firstly prepare magnesium halide alcohol compound, for example, after magnesium halide and alcohol are heated and dissolved, high pressure ejection or high speed stirring is used, and the method of solidifying into microsphere particles in a cooling medium is obtained, and the specific steps are referred to the relevant description in CN1110281A; then the magnesium halide alcohol compound particles are reacted with halogen-containing compounds such as titanium tetrachloride to prepare a magnesium-supported catalyst, during which various promoters can be added for modification. In the above-mentioned catalyst preparation process, a large amount of titanium tetrachloride needs to be used, and the excess ratio is very large. At the same time, the solid catalyst component obtained needs to be washed with a hydrocarbon solvent (such as hexane) to remove the titanium tetrachloride not loaded therein. Therefore, in the polyolefin catalyst production process, after the catalyst solid is separated and precipitated, a large amount of catalyst mother liquid containing at least one of titanium tetrachloride, unreacted hydrocarbons, unreacted halogenated alkoxy titanium, alkoxy magnesium, and unreacted esters will be generated. A large amount of waste liquid containing titanium tetrachloride is generated in the preparation process of titanium-based polypropylene catalyst, which contains a small amount of alkoxy titanium complex (for example, about 2%-5%), a small amount of lipids, and n-hexane in addition to titanium tetrachloride. If the waste liquid is directly discarded, it is bound to cause environmental pollution and waste of resources, so it is necessary to effectively utilize it.

[0003] Regarding the preparation of titanium sol, titanium-containing molecular sieve, titanium-containing catalytic material, titanium-containing catalyst and additives by titanium tetrachloride, patent CN107866211B discloses a TiO 2 Sol and catalytic cracking catalyst and method for preparing the same, the TiO 2 The titanium-chloride molar ratio of the sol is (0.2-0.6):1; and the TiO 2 Sol corrosion rate ≤ 1g / m 2 ·h, pH value is 5-8, viscosity ≥1000mPa·s at 20℃. 2Because of its high viscosity, low corrosion rate and high pH value, the sol, when used as a binder for preparing catalytic cracking catalysts, is beneficial to increase the specific surface area of ​​the catalytic cracking catalyst, improve the sphericity of the catalytic cracking catalyst, and enhance the activity of the catalytic cracking catalyst, improve the product distribution of the catalytic cracking reaction, and is mainly beneficial to the production of the target product gasoline.

[0004] Patent CN102114429B discloses a method for increasing the B acid content of ZSM-5 molecular sieve and increasing the production of light olefins. The method is to simultaneously modify the ZSM-5 molecular sieve with iron and titanium. After modification, the mass ratio of iron to titanium in the molecular sieve is 0.3-3:1, thereby improving the catalytic reactivity of the molecular sieve, promoting the conversion of long-chain alkanes and aromatics with long-chain alkyl side chains such as isopropylbenzene, and achieving the effect of significantly increasing the yield of light olefins.

[0005] Patent CN109694721B discloses a macroporous kaolinite and its preparation and application. The macroporous kaolinite contains a modified metal, and the average pore diameter is 2-50nm. The pore volume of pores with a pore diameter of 10-50nm accounts for more than 80% of the total pore volume. The modified metal is one or more of alkaline earth metals, titanium and zirconium. The preparation method of the macroporous kaolinite includes: first calcining the kaolinite; forming a mixture of the first calcined kaolinite and a first acid, water, and an optional modified metal compound, performing a first treatment, then performing a second calcination, and then forming a mixture with a second acid, water, a pore expander, and an optional modified metal compound for a second treatment, filtering, drying, and obtaining macroporous kaolinite. The modified metal compound is added in at least one step of the first treatment and the second treatment. The macroporous kaolinite can be used to prepare a cracking catalyst. The obtained catalyst has high heavy oil conversion activity, high gasoline and liquefied gas yields, low dry gas selectivity, and low coke selectivity.

[0006] Patent CN105618107B discloses a catalytic cracking catalyst and a preparation method thereof. Based on the total weight of the catalyst, the catalyst contains 10-60wt% titanium and / or zirconium modified Y molecular sieve, 10-60wt% clay and 5-50wt% binder; the titanium and / or zirconium modified Y molecular sieve contains 1.0wt%-15.0wt% titanium and / or zirconium metal oxide. The catalyst preparation method comprises the steps of preparing titanium and / or zirconium modified Y molecular sieve, preparing catalyst slurry and spray drying, wherein the titanium and / or zirconium modified Y molecular sieve comprises the following steps: (1) dispersing a titanium and / or zirconium-containing compound in water, and adjusting the pH value of the mixture to 3-10; (2) mixing the molecular sieve with the mixture obtained in step (1), stirring; optionally filtering and / or drying; (3) calcining at 300-700°C. The catalyst has a high heavy oil conversion capacity and gasoline yield.

[0007] In terms of kaolin modification, patent CN1057556C discloses a kaolin modification method, which includes calcining kaolin at 850-920°C for 10 minutes to 5 hours, and then treating the calcined kaolin at 90-150°C with a mixed acid solution having a molar ratio of 1.0-5.0 between an inorganic monobasic acid and a dibasic acid and an acid concentration of 0.4-4N for 4-40 hours. The pores of the kaolin modified by this method are concentrated in the range of 50-200 angstroms, and can be used as a component of a hydrocarbon conversion, especially a catalytic cracking catalyst.

[0008] The prior art does not involve the treatment of waste liquid containing titanium tetrachloride generated during the preparation of polypropylene catalysts. Moreover, the kaolin modification and titanium-containing kaolinite preparation processes are complicated, and acid addition and filtration treatment are required multiple times during the preparation process.

[0009] Therefore, in order to solve the problem of treating a large amount of waste liquid containing titanium tetrachloride generated during the preparation of polypropylene catalysts, and to solve the unfavorable factors of poor catalyst anti-wear performance, low activity and poor reaction selectivity, despite the recent binder and catalyst technologies, new binder and catalyst preparation technologies with simple and feasible preparation processes and excellent performance are still needed. Summary of the invention

[0010] In order to solve the above problems, the purpose of the present invention is to provide a composite binder and a preparation method and application thereof. The composite binder prepared by the preparation method can be used for the preparation of catalysts and additives, and can improve the anti-wear performance, activity, and pore volume of catalysts and additives, improve diffusion performance, promote efficient conversion of heavy oil, reduce coke formation, and improve the selectivity and performance of the reaction process.

[0011] In order to achieve the above object, the present invention provides a method for preparing a composite adhesive, which comprises the following steps:

[0012] (1) mixing calcined clay, water and titanium tetrachloride solution to obtain a mixture; (2) reacting the mixture at 40-120° C. for 0.5-6 hours to obtain the composite binder; based on the dry basis of the composite binder being 100%, the composition of the composite binder comprises 7-45wt% titanium calculated as oxide, 0.6-40wt% aluminum calculated as oxide and 30-92wt% silicon calculated as oxide.

[0013] In the preparation method of the present invention, after the clay is calcined at high temperature, the crystal structure thereof changes. For example, the silicon and aluminum contained in kaolin are mainly kaolinite structures. After being calcined at high temperature, the kaolinite undergoes a phase transformation to form active silicon and active aluminum, which can react with acid or alkali; titanium tetrachloride is hydrolyzed to produce titanium oxide and hydrogen chloride. Utilizing the above-mentioned properties of clay and titanium tetrachloride, the present invention uses calcined clay as a raw material, mixes it with water and waste liquid containing titanium tetrachloride, and reacts the hydrochloric acid produced by the hydrolysis of titanium tetrachloride with the active aluminum in the calcined clay to prepare a composite binder containing titanium and clay; because the active aluminum in the clay reacts with the hydrochloric acid produced by the hydrolysis of titanium tetrachloride, the active aluminum is separated from the clay, and medium and large pores are formed in the clay. At the same time, the active aluminum reacting with the hydrochloric acid and the fine titanium oxide particles produced by the hydrolysis jointly form a titanium-aluminum mixture, and together with the above-mentioned medium and large pore clay, a composite binder containing titanium and clay is formed.

[0014] According to a specific embodiment of the present invention, preferably, in the above preparation method, the solid content of the composite binder is 10-45wt%.

[0015] According to a specific embodiment of the present invention, preferably, in the above preparation method, in step (1), the mixed raw materials also include a dispersant; more preferably, the content of the dispersant is less than 10% based on the dry basis of the composite binder as 100%.

[0016] According to a specific embodiment of the present invention, preferably, in the above preparation method, based on the dry basis of the composite binder as 100%, the composition of the composite binder comprises 8-30wt% titanium calculated as oxide, 8-40wt% aluminum calculated as oxide, and 35-70wt% silicon calculated as oxide.

[0017] According to a specific embodiment of the present invention, preferably, in the above preparation method, the titanium tetrachloride solution is titanium tetrachloride waste liquid.

[0018] According to a specific embodiment of the present invention, preferably, in the above preparation method, the titanium tetrachloride waste liquid is a titanium tetrachloride-containing waste liquid generated in the preparation process of the polypropylene catalyst.

[0019] According to a specific embodiment of the present invention, preferably, in the above-mentioned preparation method, the titanium tetrachloride waste liquid is subjected to distillation treatment before use to separate the n-hexane organic matter therein to obtain a distillation residue containing titanium tetrachloride, and then the distillation residue containing titanium tetrachloride is used in the preparation process of the titanium-clay composite binder described in the present invention.

[0020] According to a specific embodiment of the present invention, preferably, in the above preparation method, the titanium tetrachloride solution is pure titanium tetrachloride.

[0021] According to a specific embodiment of the present invention, preferably, in the above preparation method, the clay includes one or a combination of two or more of kaolin, halloysite, montmorillonite, diatomaceous earth, halloysite, sepiolite and bentonite.

[0022] According to a specific embodiment of the present invention, preferably, in the above preparation method, the clay is one or a combination of two or more of kaolin, halloysite, diatomaceous earth, halloysite and sepiolite.

[0023] According to a specific embodiment of the present invention, preferably, in the above preparation method, the calcination is performed at 400-900° C. for 0.5-6 h.

[0024] According to a specific embodiment of the present invention, preferably, in the above preparation method, the dispersant includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene glycol.

[0025] According to a specific embodiment of the present invention, preferably, in the above preparation method, the content of the dispersant is 0.3-5%.

[0026] According to a specific embodiment of the present invention, the preparation method comprises the following specific steps: mixing clay calcined at 550-850°C for 1-3h, water, and waste liquid containing titanium tetrachloride to form a mixture, heating the mixture to 60-120°C and reacting for 0.5-3h to obtain the composite binder.

[0027] According to a specific embodiment of the present invention, preferably, in the above preparation method, in step (2), after the reaction is completed, the pH value of the reaction system is 0.5-8; more preferably, after the reaction is completed, an alkaline substance is used to adjust the pH value of the reaction system to 0.5-8; more preferably, the alkaline substance is selected from one or a combination of two or more of ammonia water, ammonium carbonate, ammonium bicarbonate, water glass, sodium aluminate, magnesium oxide, magnesium hydroxide, magnesium carbonate, calcium oxide, calcium hydroxide, and calcium carbonate.

[0028] According to a specific embodiment of the present invention, preferably, in step (1), the clay is crushed to an average particle size D (v, 0.5) < 4 μm before or after calcination, and then mixed with water and titanium tetrachloride solution.

[0029] The present invention also provides a composite binder obtained by the above preparation method, wherein, based on the dry basis of the composite binder as 100%, the composition of the composite binder comprises 7-45wt% titanium calculated as oxide, 0.6-40wt% aluminum calculated as oxide, and 30-92wt% silicon calculated as oxide.

[0030] The present invention also provides application of the composite binder in preparing a catalytic cracking aid.

[0031] The present invention also provides a method for treating titanium tetrachloride waste liquid, which adopts the above-mentioned preparation method.

[0032] According to a specific embodiment of the present invention, preferably, in the above-mentioned method for treating titanium tetrachloride waste liquid, the titanium tetrachloride waste liquid is a waste liquid containing titanium tetrachloride generated in the process of preparing a polypropylene catalyst.

[0033] The waste liquid containing titanium tetrachloride generated in the process of preparing polypropylene catalyst has a titanium tetrachloride content of about 80%-95% (by weight). If it is discharged into the environment, it will inevitably cause environmental pollution and waste of resources, and the separate treatment of the waste liquid containing titanium tetrachloride will also increase the treatment cost and expense. The present invention uses the waste liquid containing titanium tetrachloride generated in the process of preparing polypropylene catalyst to prepare a composite binder containing clay, which not only solves the problem of utilizing the waste liquid containing titanium tetrachloride and avoids its environmental pollution, but also avoids the shortcomings of the prior art. The composite binder containing titanium and clay prepared by the method can be used for the preparation of hydroprocessing catalysts, catalytic cracking catalysts, catalytic cracking catalysts, and catalytic cracking additives, and can improve the anti-wear performance and activity of catalysts and additives, increase the pore volume of catalysts and improve the diffusion performance, thereby promoting the efficient conversion of heavy oil, reducing coke formation, and improving the selectivity of the reaction process.

[0034] The present invention has the following advantages and effects:

[0035] (1) The composite binder containing titanium and clay provided by the present invention uses calcined clay as a raw material, and uses hydrochloric acid produced by the hydrolysis of titanium tetrachloride to extract the active aluminum in the calcined clay, thereby forming medium and macropores in the clay and also forming a mixture containing titanium and aluminum. Compared with the prior art, the clay modification process of the present invention does not require the addition of acid, and a composite binder with better bonding performance and containing medium and macropore acid-extracted clay can be obtained;

[0036] (2) The composite binder containing titanium and clay provided by the present invention has a simple and feasible preparation process, an adjustable pH value, and the titanium content can be adjusted within a large range; the composite binder containing titanium and clay provided by the present invention uses waste liquid containing titanium tetrachloride, which not only solves the problem of treating the waste liquid and avoids its pollution of the environment, but also reduces the high treatment cost of the waste liquid. At the same time, the use of this composite binder to prepare a catalyst can improve the anti-wear performance, activity, and pore volume of the catalyst, and can promote the efficient conversion of heavy oil, reduce coking, and improve reaction selectivity. DETAILED DESCRIPTION

[0037] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0038] In the following examples, the element content in the sample was determined by X-ray fluorescence analysis. The wear index of the additive was analyzed by the MS-C / 6 wear index analyzer produced by Shenyang Kehui Instrument Manufacturing Co., Ltd. The pore volume of the additive was determined by the water drop method. The catalytic cracking reaction performance of the additive was evaluated on the heavy oil micro-reactor evaluation device (ACE). The additive was pre-aged at 800°C and 100% water vapor for 17 hours and then mixed evenly with the LDC-200 balance agent at a weight ratio of 9:1.

[0039] The origin and specifications of the raw materials used are as follows:

[0040] (1) Waste liquid containing titanium tetrachloride (hereinafter referred to as waste liquid containing titanium tetrachloride) generated during the preparation of polypropylene catalyst: titanium content 90% (in terms of TiCl 4 Calculated), provided by Lanzhou Chemical Research Center of PetroChina Petrochemical Research Institute; kaolin (29wt% loss on ignition), halloysite (16.6wt% loss on ignition), alumina sol (containing 21.6wt% alumina), ZSM-5 molecular sieve (silicon-aluminum ratio 30, 8wt% loss as appropriate), LDC-200 industrial balanced catalyst: all are industrial products, collected from the catalyst plant of Lanzhou Petrochemical Company.

[0041] (2) Diatomaceous earth (ignition loss 2.6 wt%): industrial product, purchased from Inner Mongolia;

[0042] (3) Titanium tetrachloride, oxalic acid, polyethylene glycol, carboxymethyl cellulose: all chemical reagents;

[0043] (4) Hydrochloric acid: concentration 36%, chemical reagent; Ammonia water: concentration 18%, chemical reagent.

[0044] Preparation Example 1

[0045] This preparation example provides a composite binder containing titanium and clay, and the preparation method thereof is as follows:

[0046] The kaolin was calcined at 750°C for 2 hours to obtain a calcined material, 1674 g (dry basis) of the calcined material was crushed to an average particle size D (v, 0.5) < 4 μm, 5.16 L of decationized water was added and stirred, 332 g of waste liquid containing titanium tetrachloride and 18 g of polyethylene glycol were added, the temperature was raised to 70°C, and stirred for 1 hour. The pH value was 3.5 to obtain the titanium-clay composite binder M-1.

[0047] The composition of the composite binder M-1 containing titanium and clay is: 93wt% (dry basis) of kaolin roasted material, 7wt% (titanium oxide) of titanium from waste liquid containing titanium tetrachloride, and the solid content of the composite binder M-1 is 25wt%.

[0048] Preparation Example 2

[0049] This preparation example provides a composite binder containing titanium and clay, and the preparation method thereof is as follows:

[0050] The halloysite is crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 600° C. for 5 hours to obtain a calcined material. 1499 g (dry basis) of the calcined material is added to 7.3 L of decationized water and stirred, and 793 g of waste liquid containing titanium tetrachloride is added. The temperature is raised to 90° C. and stirred for 2 hours. The pH value is adjusted to 2.5 with ammonia water to obtain the titanium-clay composite binder M-2.

[0051] The composition of the composite binder M-2 containing titanium and clay is: 83.3wt% (dry basis) of halloysite calcined material, 16.7wt% (titanium oxide) of titanium from waste liquid containing titanium tetrachloride, and the solid content of the composite binder M-2 is 18wt%.

[0052] Preparation Example 3

[0053] This preparation example provides a composite binder containing titanium and clay, and the preparation method thereof is as follows:

[0054] Kaolin and diatomaceous earth are respectively crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 850° C. for 2.5 hours to obtain a calcined material. 900 g (dry basis) of kaolin calcined material, 100.8 g (dry basis) of diatomaceous earth calcined material, and 72 g of carboxymethyl cellulose are added to 2.0 L of decationized water and stirred. 2109 g of waste liquid containing titanium tetrachloride is added, the temperature is raised to 60° C., stirred for 3 hours, and the pH value is adjusted to 3.0 with ammonia water to obtain the titanium-clay composite binder M-3.

[0055] The composition of the titanium-clay-containing composite binder M-3 is: 50wt% (dry basis) of kaolin calcined material, 5.6wt% (dry basis) of diatomaceous earth calcined material, 44.4wt% (calculated as titanium oxide) of titanium from waste liquid containing titanium tetrachloride, and the solid content of the composite binder M-3 is 30wt%.

[0056] Preparation Example 4

[0057] This preparation example provides a composite binder containing titanium and clay, and the preparation method thereof is as follows:

[0058] The kaolin was crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 850°C for 2 hours to obtain a calcined material. 1674 g (dry basis) of the calcined material was added to 5.19 L of decationized water and stirred, 299 g of titanium tetrachloride and 9 g of polyethylene glycol were added, the temperature was raised to 85°C, and stirred for 4 hours. The pH value was 3.6 to obtain the titanium-clay composite binder M-4.

[0059] The composition of the composite binder M-4 containing titanium and clay is: 93wt% (dry basis) of kaolin calcined material, 7wt% (titanium oxide) of titanium from titanium tetrachloride, and the solid content of the composite binder M-4 is 25wt%.

[0060] Preparation Comparative Example 5

[0061] This preparation comparative example provides a comparative binder containing titanium and clay without being calcined, and its preparation method is as follows:

[0062] 1674 g (dry basis) of kaolin was pulverized to an average particle size D (v, 0.5) < 4 μm, and 4.2 L of decationized water was directly added without calcination and stirred. 332 g of waste liquid containing titanium tetrachloride and 18 g of polyethylene glycol were added. The temperature was raised to 70°C and stirred for 1 hour. The pH value was adjusted to 3.5 with ammonia water to obtain a comparative binder DM-1 containing titanium and clay.

[0063] The composition of the comparative binder DM-1 containing titanium and clay is: 93 wt% kaolin (on a dry basis), 7 wt% titanium from waste liquid containing titanium tetrachloride (on a titanium oxide basis), and the solid content of the comparative binder DM-1 is 25 wt%.

[0064] Preparation Comparative Example 6

[0065] This preparation example provides a modified kaolin, which is prepared according to the method of Example 8 of preparing macroporous kaolinite disclosed in CN109694721B. The specific preparation method is as follows:

[0066] The kaolin was calcined at 750°C for 2 hours to obtain a calcined material (referred to as the first calcined material), 1680 g (dry basis) of the calcined material was added with decationized water (pH=3.1, the same below) and stirred to prepare a slurry with a solid content of 25 wt%, 5000 g of 1 mol / L hydrochloric acid and 1000 g of oxalic acid and 120 g of titanium tetrachloride (analytical grade) were added, the temperature was raised to 70°C, the stirring time was 1 hour, and then the mother liquor was removed by filtration, and the filter cake was dried to obtain the first step product; the first step product was 1200g was calcined at 750°C for 2 hours to obtain a calcined material (called the second calcined material), 1000g (dry basis) of the second calcined material was added with decationized water and stirred to obtain a slurry with a solid content of 25wt%, 2000g of 1mol / L hydrochloric acid, 500g of oxalic acid, 500g of polyethylene glycol, and 70g of titanium tetrachloride (analytical grade) were added, the temperature was raised to 70°C, the stirring time was 1 hour, and then the mother liquor was filtered out, the filter cake was dried to obtain a macroporous kaolinite comparison sample DM-2.

[0067] The titanium content of the macroporous kaolinite comparative sample DM-2 is 6.9 wt % (calculated as titanium oxide).

[0068] Preparation Comparative Example 7

[0069] This comparative preparation example prepares a comparative binder DM-3 according to the method of Preparation Example 3, except that no ammonia water is used to adjust the pH value. The preparation method is as follows:

[0070] Kaolin and diatomaceous earth were respectively crushed to an average particle size D (v, 0.5) < 4 μm, and calcined at 850°C for 2.5 hours to obtain a calcined material. 900 g (dry basis) of kaolin calcined material, 100.8 g (dry basis) of diatomaceous earth calcined material, and 72 g of carboxymethyl cellulose were added to 2.0 L of decationized water and stirred, and 2109 g of waste liquid containing titanium tetrachloride was added, the temperature was raised to 60°C, and stirred for 3 hours to obtain a comparative binder DM-3 containing titanium and clay.

[0071] The composition of the comparative binder DM-3 containing titanium and clay is: 50 wt% (dry basis) of calcined kaolin, 5.6 wt% (dry basis) of calcined diatomaceous earth, and 44.4 wt% (titanium oxide) of titanium from waste liquid containing titanium tetrachloride.

[0072] The spray drying methods of the catalytic cracking aids of the following Examples 1-4 and Comparative Examples 1-4 adopt the following process conditions: the furnace temperature of the spray tower is controlled at 450°C, the spray tail gas temperature is controlled at 200°C, and the particle size range of the obtained catalytic cracking aid is 65-78 μm.

[0073] Example 1

[0074] This embodiment provides a catalytic cracking aid, and the preparation method thereof is as follows:

[0075] Add 200 g (dry basis) of composite binder M-1, 130 g of aluminum sol (alumina), and 796 g of decationized water into a reactor, stir, add 320 g (dry basis) of kaolin, and then add 350 g (dry basis) of ZSM-5 molecular sieve, stir for 30 minutes, and subject the obtained slurry to sand milling so that the average particle size D (v, 0.5) of the slurry is less than 4 μm, spray dried, and the obtained microspheres are calcined at 570°C for 2 hours to obtain catalytic cracking aid CAT-1.

[0076] The composition of the catalytic cracking aid CAT-1 is: 32 wt% (dry basis) of kaolin, 20 wt% (dry basis) of the composite binder M-1, 13 wt% of alumina from the aluminum sol, 35 wt% (dry basis) of the ZSM-5 molecular sieve, and the gelled solid content of the catalytic cracking aid CAT-1 is 33%. The properties of the aid CAT-1 are shown in Table 1.

[0077] Example 2

[0078] This embodiment provides a catalytic cracking aid, and the preparation method thereof is as follows:

[0079] Add 100 g (dry basis) of composite binder M-2, 130 g of aluminum sol (alumina), and 501 g of decationized water into a reactor, stir, add 420 g (dry basis) of kaolin, and then add 350 g (dry basis) of ZSM-5 molecular sieve, stir for 30 minutes, and subject the obtained slurry to sand milling so that the average particle size D (v, 0.5) of the slurry is less than 4 μm, spray dried, and the obtained microspheres are calcined at 570°C for 2 hours to obtain catalytic cracking aid CAT-2.

[0080] The composition of the catalytic cracking aid CAT-2 is: 42 wt% (dry basis) of kaolin, 10 wt% (dry basis) of the oxide from the composite binder M-2, 13 wt% of alumina from the aluminum sol, 35 wt% (dry basis) of the ZSM-5 molecular sieve, and the gelled solid content of the catalytic cracking aid CAT-2 is 38%. The properties of the aid CAT-2 are shown in Table 1.

[0081] Example 3

[0082] This embodiment provides a catalytic cracking aid, and the preparation method thereof is as follows:

[0083] Add 260 g (dry basis) of composite binder M-3 and 980 g of decationized water into a reactor, stir, add 390 g (dry basis) of kaolin, then add 350 g (dry basis) of ZSM-5 molecular sieve, stir for 30 min, sand grind the resulting slurry to make the average particle size D (v, 0.5) of the slurry less than 4 μm, spray dry, and calcine the resulting microspheres at 570 ° C for 2 h to obtain catalytic cracking aid CAT-3.

[0084] The composition of the catalytic cracking aid CAT-3 is: 39 wt% (dry basis) of kaolin, 26 wt% (dry basis) of the oxide from the composite binder M-3, 35 wt% (dry basis) of the ZSM-5 molecular sieve, and the gelled solid content of the catalytic cracking aid CAT-3 is 36%. The properties of the aid CAT-3 are shown in Table 1.

[0085] Example 4

[0086] This embodiment provides a catalytic cracking aid, and the preparation method thereof is as follows:

[0087] Add 200 g (dry basis) of composite binder M-4, 130 g of aluminum sol (alumina), and 796 g of decationized water into a reactor, stir, add 320 g (dry basis) of kaolin, and then add 350 g (dry basis) of ZSM-5 molecular sieve, stir for 30 minutes, and subject the obtained slurry to sand milling so that the average particle size D (v, 0.5) of the slurry is less than 4 μm, spray dried, and the obtained microspheres are calcined at 570°C for 2 hours to obtain catalytic cracking aid CAT-4.

[0088] The composition of the catalytic cracking aid CAT-4 is: 32 wt% (dry basis) of kaolin, 20 wt% (dry basis) of the composite binder M-4, 13 wt% of alumina from the aluminum sol, 35 wt% (dry basis) of the ZSM-5 molecular sieve, and the gelled solid content of the catalytic cracking aid CAT-4 is 33%. The properties of the aid CAT-4 are shown in Table 1.

[0089] Comparative Example 1

[0090] This comparative example provides a catalytic cracking aid, and its preparation method is as follows:

[0091] 200 g (dry basis) of comparative binder DM-1, 130 g of aluminum sol (alumina), and 796 g of decationized water were added to a reactor, stirred, 320 g (dry basis) of kaolin was added, and then 350 g (dry basis) of ZSM-5 molecular sieve was added, stirred for 30 min, the obtained slurry was sand milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, spray dried, and the obtained microspheres were calcined at 570°C for 2 h to obtain a comparative catalytic cracking aid DCAT-1.

[0092] The composition of the comparative catalytic cracking aid DCAT-1 is: 32wt% (dry basis) of kaolin, 20wt% (dry basis) of the comparative binder DM-1, 13wt% of alumina from the aluminum sol, 35wt% (dry basis) of the ZSM-5 molecular sieve, and the gelled solid content of the comparative catalytic cracking aid DCAT-1 is 33%. The performance of the comparative aid DCAT-1 is shown in Table 1.

[0093] Comparative Example 2

[0094] This comparative example provides a catalytic cracking aid, and its preparation method is as follows:

[0095] In a reactor, 100 g (dry basis) of the macroporous kaolinite comparison sample DM-2 prepared in Preparation Example 6, 160 g of aluminum sol (alumina basis), and 842 g of decationized water were added, and stirred. 390 g (dry basis) of kaolin was added, and then 350 g (dry basis) of ZSM-5 molecular sieve was added, and stirred for 30 minutes. The obtained slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and spray-dried. The obtained microspheres were calcined at 570°C for 2 hours to obtain a comparative catalytic cracking aid DCAT-1.

[0096] The composition of the comparative catalytic cracking aid DCAT-2 is: 39wt% (dry basis) of kaolin, 10wt% (dry basis) of the oxide from the macroporous kaolinite comparative sample DM-2, 16wt% of alumina from the aluminum sol, 35wt% (dry basis) of the ZSM-5 molecular sieve, and the gel solid content of the comparative catalytic cracking aid DCAT-2 is 38%. The performance of the comparative aid DCAT-2 is shown in Table 1.

[0097] Comparative Example 3

[0098] This comparative example provides a catalytic cracking aid, and its preparation method is as follows:

[0099] In a reactor, 260 g (dry basis) of the comparative binder DM-3 prepared in Preparation Example 7 and 980 g of decationized water were added, and the mixture was stirred. 390 g (dry basis) of kaolin was added, and then 350 g (dry basis) of ZSM-5 molecular sieve was added, and the mixture was stirred for 30 min. The resulting slurry was sand-milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm, and the mixture was spray-dried. The resulting microspheres were calcined at 570 ° C for 2 h to obtain a catalytic cracking aid DCAT-3.

[0100] The composition of the catalytic cracking aid DCAT-3 is: 39 wt% (dry basis) of kaolin, 26 wt% (dry basis) of the oxide from the comparative binder DM-3, 35 wt% (dry basis) of the ZSM-5 molecular sieve, and the gelled solid content of the catalytic cracking aid DCAT-3 is 36%. The performance of the comparative aid DCAT-3 is shown in Table 1.

[0101] Comparative Example 4

[0102] This comparative example provides a catalytic cracking aid, and its preparation method is as follows:

[0103] Add 819 g of decationized water into the reactor and stir. Add 490 g (dry basis) of kaolin and 160 g of aluminum sol (alumina) and then add 350 g (dry basis) of ZSM-5 molecular sieve and stir for 30 min. The obtained slurry is sand milled to make the average particle size D (v, 0.5) of the slurry less than 4 μm. Spray dry the obtained microspheres and calcine them at 570 ° C for 2 h to obtain a comparative catalytic cracking aid DCAT-4.

[0104] The composition of the comparative catalytic cracking aid DCAT-4 is: 49wt% kaolin (dry basis), 16wt% alumina from aluminum sol, 35wt% ZSM-5 molecular sieve (dry basis), and the gel solid content of the comparative catalytic cracking aid DCAT-4 is 38%. The analytical test results of the anti-wear performance and pore volume are shown in Table 1.

[0105] Table 1 Performance test results of catalytic cracking additives Examples 1-4 and Comparative Examples 1-4

[0106] Catalytic cracking additives Wear index, m% / h Pore ​​volume, mL / g CAT-1 1.5 0.39 CAT-2 1.6 0.37 CAT-3 1.2 0.45 CAT-4 1.6 0.39 DCAT-1 11.2 — DCAT-2 1.9 0.37 DCAT-3 1.1 0.42 DCAT-4 1.7 0.33

[0107] The results in Table 1 show that the wear index of DCAT-1 is too high and cannot meet the use requirements of the additive (generally the wear index should be less than 3.5%); compared with DCAT-1, the additive CAT-1 has a low wear index and good anti-wear performance. Compared with DCAT-2, the additive CAT-2 has a lower wear index and no decrease in pore volume when the aluminum sol content is reduced by 3 percentage points, showing excellent anti-wear performance and the characteristics of increasing the pore volume and improving the pore structure of the additive; compared with DCAT-4, CAT-3, even without the addition of the binder aluminum sol, still has better anti-wear performance and higher pore volume, and also shows excellent anti-wear performance and the performance characteristics of increasing the pore volume and improving the pore structure of the additive.

[0108] Compared with the catalytic cracking aids DCAT-2 and DCAT-4 prepared in Comparative Examples 2 and 4, although the amount of aluminum sol added as a binder in the aid is reduced, the wear index of the catalytic cracking aids CAT-1, CAT-2, and CAT-3 is lower, and the pore volume of the water drop method is larger, indicating that the use of the titanium-containing and clay composite binder provided by the present invention is beneficial to improving the wear resistance of the catalytic cracking aid, while improving the pore structure of the aid and increasing the pore volume of the aid, which helps to improve the catalytic cracking reaction selectivity and performance of the aid.

[0109] The evaluation results of the catalytic cracking reaction performance of the additive are shown in Table 2.

[0110] Table 2 Evaluation results of reaction performance of catalytic cracking aid examples 1-4 and comparative examples 1-4

[0111] Catalytic cracking additives Conversion rate, m% Heavy oil, m% Coke, m% CAT-1 86.75 4.16 8.69 CAT-2 86.47 4.28 8.80 CAT-3 86.94 4.02 8.58 CAT-4 86.42 4.20 8.71 DCAT-1 85.96 4.84 9.26 DCAT-2 86.41 4.36 8.92 DCAT-3 85.73 4.91 9.30 DCAT-4 85.40 4.95 9.43

[0112] The results in Table 2 show that compared with the comparative additives DCAT-1, DCAT-2, DCAT-3, and DCAT-4 of Comparative Examples 1-4, when the catalytic cracking additives CAT-1, CAT-2, CAT-3, and CAT-4 of the present invention are added to the LDC-200 industrial equilibrium catalyst, the conversion rate of the catalytic cracking reaction is improved, the heavy oil yield is reduced, and the coke yield is reduced, indicating that the additive prepared by the technology of the present invention can promote the conversion of heavy oil, reduce coking, and improve the selectivity of the catalytic reaction.

Claims

1. A method for preparing a composite adhesive, comprising the following steps: (1) mixing calcined clay, water and titanium tetrachloride solution to obtain a mixture; (2) reacting the mixture at 40-120° C. for 0.5-6 hours to obtain the composite binder; Calculated based on the dry basis of the composite binder as 100%, the composition of the composite binder includes 7-45wt% titanium calculated as oxide, 0.6-40wt% aluminum calculated as oxide, and 30-92wt% silicon calculated as oxide.

2. The preparation method according to claim 1, wherein The solid content of the composite binder is 10-45wt%.

3. The preparation method according to claim 1, wherein In step (1), the mixed raw materials also include a dispersant, and the content of the dispersant is less than 10% based on the dry basis of the composite binder being 100%.

4. The preparation method according to claim 1, wherein Taking the dry basis of the composite binder as 100%, the composition of the composite binder comprises 8-30 wt % of titanium calculated as oxide, 8-40 wt % of aluminum calculated as oxide, and 35-70 wt % of silicon calculated as oxide.

5. The preparation method according to claim 1, wherein The titanium tetrachloride solution is titanium tetrachloride waste liquid; Preferably, the titanium tetrachloride waste liquid is a titanium tetrachloride-containing waste liquid generated during the preparation of a polypropylene catalyst; Preferably, the titanium tetrachloride waste liquid is distilled before use to remove n-hexane.

6. The preparation method according to claim 1, wherein The clay includes one or a combination of two or more of kaolin, halloysite, montmorillonite, diatomaceous earth, halloysite, sepiolite and bentonite; Preferably, the clay is one or a combination of two or more of kaolin, halloysite, diatomite, halloysite and sepiolite.

7. The preparation method according to claim 1, wherein The calcination is carried out at 400-900° C. for 0.5-6 h.

8. The preparation method according to claim 3, wherein: The dispersant includes one or a combination of two or more of 1,3,5-trimethylbenzene, 1,3,5-triisopropylbenzene, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene glycol; Preferably, the content of the dispersant is 0.3-5%.

9. The preparation method according to claim 1, wherein The preparation method comprises the following steps: mixing clay calcined at 550-850°C for 1-3h, water and waste liquid containing titanium tetrachloride to form a mixture, heating the mixture to 60-120°C and reacting the mixture for 0.5-3h to obtain the composite binder.

10. The preparation method according to claim 1, wherein: In step (2), after the reaction is completed, the pH value of the reaction system is 0.5-8; Preferably, after the reaction is completed, an alkaline substance is used to adjust the pH value of the reaction system to 0.5-8; Preferably, in step (1), the clay is crushed to an average particle size D(v, 0.5) < 4 μm before or after calcination, and then mixed with water and titanium tetrachloride solution.

11. The composite binder prepared by the preparation method according to any one of claims 1 to 10, wherein: Calculated based on the dry basis of the composite binder as 100%, the composition of the composite binder includes 7-45wt% titanium calculated as oxide, 0.6-40wt% aluminum calculated as oxide, and 30-92wt% silicon calculated as oxide.

12. Use of the composite binder according to claim 11 in preparing a catalytic cracking aid.

13. A method for treating titanium tetrachloride waste liquid, which adopts the preparation method according to any one of claims 1 to 10; Preferably, the titanium tetrachloride waste liquid is a titanium tetrachloride-containing waste liquid generated during the preparation of a polypropylene catalyst.

Citation Information

Patent Citations

  • Method for improving B acid content of ZSM-5 molecular sieve and realizing yield increase of light olefin

    CN102114429B

  • Propylene polymerization catalyst

    CN102336851B

  • A fluid catalytic cracking catalyst and its preparation method

    CN105618107B

  • Process for modifying kaolin

    CN1057556C

  • A polypropylene catalyst component, preparation method and catalyst thereof

    CN107434832B